Optimalisasi Peran Kader Kesehatan Dalam Penerapan Manajemen Fatigue - Endang Supriyanti; Menik Kustriyani (Lembaga Pengembangan Kinerja Dosen, 2024)
The Healthy Indonesia Program through a family approach seeks to encourage community independence to live a healthy life. This effort requires the involvement of various parties, including health cadres as intermediaries/liaisons between the community and health workers. Health cadres are community members who are selected and provided with health skills through training by health service facilities or local health centers. Health cadres also need to be given training on fatigue management because every individual can experience fatigue which will be a source of health problems for both individuals and families. Fatigue is a common symptom of many mild to serious medical conditions, even leading to death. The purpose of this community service activity is to provide fatigue management training to health cadres. The specific target of this PKM activity is the implementation of health education and training on fatigue management for health cadres in RW 13 Beringin Village. The method used is training, including providing health education on fatigue management, training cadres to carry out non-pharmacological fatigue therapy and assistance in the application of non-pharmacological fatigue therapy, evaluation of activities carried out by giving pre and posttest questionnaires on fatigue management. The results of community service most of the participants, 60%, have good knowledge, participants are able to demonstrate autogenic relaxation correctly and apply it in everyday life and inform residents during posbindu activities.